2004
DOI: 10.1124/jpet.104.077230
|View full text |Cite
|
Sign up to set email alerts
|

YC-1 [3-(5′-Hydroxymethyl-2′-furyl)-1-benzyl Indazole] Exhibits a Novel Antiproliferative Effect and Arrests the Cell Cycle in G0-G1 in Human Hepatocellular Carcinoma Cells

Abstract: This study delineates the antiproliferative activities and in vivo efficacy of YC-1 [3-(5Ј-hydroxymethyl-2Ј-furyl)-1-benzyl indazole] in human hepatocellular carcinoma cells. YC-1 inhibited the growth of HA22T and Hep3B cells in a concentrationdependent manner without significant cytotoxicity. YC-1 induced G 1 phase arrest in the cell cycle, as detected by an increase in the proportion of cells in the G 1 phase using FACScan flow cytometric analysis. It was further shown that cGMP, p42/p44 mitogen-activated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Because both HIF-1a inhibition and S-phase arrest were induced by YC-1 at <5 Amol/L, we believe that these effects are responsible for tumor growth inhibition by YC-1. However, a recent report (22) showed that YC-1 at >50 Amol/L induced G 1 -phase arrest in hepatoma cell lines. This concentration is much higher (10 fold) than the tumor levels of YC-1 in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Because both HIF-1a inhibition and S-phase arrest were induced by YC-1 at <5 Amol/L, we believe that these effects are responsible for tumor growth inhibition by YC-1. However, a recent report (22) showed that YC-1 at >50 Amol/L induced G 1 -phase arrest in hepatoma cell lines. This concentration is much higher (10 fold) than the tumor levels of YC-1 in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…This S-phase arrest was not peculiar to a single cell type as it occurred in both HT29 and HCT116 colorectal cancer cell lines. At similar concentrations, YC-1 has been reported to induce G 0 /G 1 arrest in human hepatocellular carcinoma (23) and human umbilical vein endothelial cells (24). The mechanism by which YC-1 induces cell cycle arrest at different phases in different cell types is unknown but may depend on the individual cell type and/or culture conditions, including culture density and serum concentration.…”
Section: Discussionmentioning
confidence: 97%
“…In preliminarily studies, we demonstrated that treatment with high concentrations (Ͼ50 M) of YC-1 results in growth inhibition of hepatocellular carcinoma cells (HA22T) (Wang et al, 2005) or apoptosis of prostate cancer cells (PC-3) and leukemia cancer cells (HL-60 and CCRF-CEM) in culture (data not shown). Thus, the growth-inhibitory action of YC-1 at low concentration is considered to be a more specific effect on endothelial cells that are stimulated by angiogenic growth factors.…”
Section: Discussionmentioning
confidence: 99%